MANAJEMEN KEPALA MADRASAH DALAM MENGATASI PROBLEMATIKA GURU MADRASAH DI KEPULAUAN TERPENCIL - Eka Nurhayati; Anita Puji Astutik (JURNAL TARBIYAH, 2024)
This research describes the management of madrasah principals in overcoming teacher problems or problems in one of the madrasahs located on one of the remote islands in the Sapeken sub-district, Sumenep Regency. Some of the roles of madrasah heads are to improve teacher qualifications by helping find ways for alumni to continue to higher education. Another role of the school principal is that the principal helps manage School Operational Assistance funds for charitable efforts so that teacher welfare remains guaranteed. Apart from that, as a school manager and administrator, the principal provides online-based training so that it remains accessible to teachers. This research is a type of case study research or field research using a qualitative approach. This research data was collected through several stages including observation, interviews and documentation. This research aims to collect and describe data and then critically analyze the problematic problems of madrasa teachers in remote islands to find solutions to research problems.